MASATO-DRIKNINGENS SOCIALE RUM: Ashéninkasamfundet i Gran Pajonal - Veber, Hanne (Tidsskriftet Antropologi, 1998)
Hanne Veber: The Social Space of Masato Drinking and Ashéninka Society in the Gran Pajonal Ashéninka natives in the Gran Pajonal, an isolated area with small and widely dispersed settlements in the Upper Amazon of eastem Peru, are fond of drinking masato to the point of even distinguishing themselves as “the ones who drink masato”. Masato is a homebrewed beer made from manioc, the staple crop and basis of Ashéninka subsistence. Ashéninka from different settlements regularly gather for communal drinkingbouts that get entire communities solidly intoxicated on masato for two or more days. The article considers the phenomenon in terms of its performative capacity for invoking codified meanings and forms of interaction central to Ashéninka social life. From this perspective, the communal drinking-bout becomes a symbolic medium of communication where the code for being Ashéninka is enacted and reiterated. This implies a social coherence, perhaps the existence of the thing otherwise refered to by the term “society”. It includes the scattered and independent settlement of Ashéninka who adhere to the code and contribute to its reproduction. This society, however, is not an interrelated series of parts that make up a whole plus something else in the Durkheimian sense of “the social”. It is rather a symbolically constructed horizon of possibilities and expectations, always provisional and emergent. Masato, then, is the developer through which the contours of this Ashéninka society become visible.